On the numerical solving of one minimization problem - Čiegis, Raimondas; Pakenienė, Violeta (Lietuvos matematikos rinkinys, 2002)
In this paper we consider the dependence of iterative methods convergence rate on iterative parameters selection. We propose the numerical algorithm determination of the optimal iterative parameters. Using it we solve classical minimization 2D and 3D problems and modificate 2D and 3D minimization problems and analyse the convergence rate dependence on the matrix spectral characteristics.